A clinical trial to assess the blood loss in women predisposed to postpartum hemorrhage with the use of prophylactic intravenous tranexamic acid - Satyasri, K.; C., Chandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Postpartum hemorrhage (PPH), a complication encountered during third stage of labour, contributes to 25% of maternal death worldwide. Despite various measures for prevention and management of PPH, burden of PPH still looms. Methods: Prospective randomized controlled clinical trial (RCT) was conducted in Vydehi Institute of Medical Sciences, among 128 patients predisposed to PPH, over 18 months. After meeting the inclusion and exclusion criteria, participants were randomized to receive tranexamic acid (TXA) intravenously 10 mg/kg along with 10 IU of oxytocin following the delivery. Patients were analysed for, blood loss, need for medical or surgical interventions. Results: Parameters like age, mean gestational age at haemoglobin estimation, and at delivery were similar among groups. The need or parenteral iron, blood transfusions, uterine artery ligation and compression suture were higher in controls group, but not statistically significant. Among the cesarean section (CS) group, most significant pre-disposing factors for PPH were previous CS (p value=0.012) and anaemia (p value =0.01). Incidence of PPH 0.69% (p value =0.031) and use of additional uterotonics were statistically significant (p value <0.05). Among the vaginal delivery (VD) group, most significant pre-disposing factors were anaemia (p value =0.002), thrombocytopenia (p value =0.045), and fetal-macrosomia (p value =0.020). Incidence of PPH 0.25% (p value <0.001) and use of additional uterotonics and hospital stay were statistically significant. Conclusions: We conclude that, anemic patients were at higher risk of PPH irrespective of the mode of delivery. Prophylactic TXA lowers incidence of PPH, blood loss, use of additional uterotonics and hospital stay even in the presence of pre-disposing factors. Quantification of blood loss is better estimated by drop in haemoglobin after 24 hours.